The influence of repeated frowning and smiling on corrugator muscle activity and wrinkles between eyebrows - Shuntaro Okazaki; Makito Suzuki; Keith Kawabata Duncan (Scientific Reports)
Abstract Like the lines themselves, concerns about facial wrinkles, particularly glabellar lines - the prominent furrows between the eyebrows - intensify with age. These lines can inadvertently convey negative emotions due to their association with negative facial expressions. We investigated the effects of repeated frowning on the development of temporary glabellar lines through the activation of the corrugator muscle. In addition, as communication via facial expressions requires precise control over the muscles of the face in such a way as to avoid contradictory signals, we hypothesized that smiling and activation of the zygomatic major may inhibit the corrugator. Our findings reveal that repeated frowning creates temporary wrinkles between the eyebrows, caused by the slight but cumulative activation of the corrugator muscle. Further we found that the act of smiling activates zygomatic major and suppresses the corrugator reducing the appearance of glabellar lines. The results offer a novel perspective on smiling and suggests that smiling not only facilitates positive emotional exchanges but may also help maintain a youthful facial appearance.